PENGARUH PERSISTENSI LABA, KUALITAS AUDITOR, DAN TATA KELOLA PERUSAHAAN TERHADAP BIAYA UTANG BUMN SEKTOR NON-KEUANGAN - Nuriyatul Mustofiyah; Puji Handayati (Jurnal Bisnis dan Akuntansi, 2023)
This research purposes to ascertain how corporate governance, auditor quality, and profit persistence affect cost of debt. The information used in this study comes from the annual reports of non-financial sector state-owned companies that were included on the IDX between 2017 and 2022. Purposive sampling was used to choose the sample for this investigation, yielding up to 52 data points from a total of 102 data points. Multiple linear regression analysis was employed in this study's data analysis. The findings revealed that corporate governance has a negative impact on the cost of debt whereas earnings persistence has a positive impact. Meanwhile, the quality of auditors has no influence on the cost of debt.